Optimisation of conditions for the formation of spheroids of head and neck squamous cell carcinoma cell lines for use as animal alternatives - Tenschert, Esther; Kern, Johann; Affolter, Annette; Rotter, Nicole; Lammert, Anne (Alternatives to laboratory animals, 2022)
The use of in vitro 3-D cell culture models in cancer research has yielded substantial gains in knowledge on various aspects of tumour biology. Such cell culture models could be useful in the study of head and neck squamous cell carcinoma (HNSCC), where mimicking intratumoral and intertumoral heterogeneity is especially challenging. Our research aims to establish 3-D spheroid models for HNSCC that reproduce in vitro the connections between tumour cells and the surrounding microenvironment. The aims of this study were to determine the optimal conditions for the culture and use of spheroids from HNSCC cell lines and optimal timepoint for using the spheroids obtained, to evaluate the effects of coculture with tumour-specific fibroblasts on spheroid formation, and to investigate spheroid responses to cisplatin treatment. Four HNSCC cell lines (UMSCC-11A, UMSCC-11B, UMSCC-22B and UD-SCC-01) were seeded in flat or round bottom well ultra-low attachment spheroid plates, and spheroid formation was evaluated. The HNSCC cell lines were then cocultured with stromal cells of the tumour microenvironment, producing an accelerated formation of dense spheroids. The viability of cells within the spheroids was assessed during cell culture by using a fluorescent dye. Our results suggest that: three out of the four cell lines tested could form usable spheroids with acceptable viability; the addition of stromal cells did not improve the number of viable cells; and the use of round bottom well plates supported the formation of a single spheroid, whereas flat bottom well plates led to the formation of multiple spheroids of different sizes.